MONITORING AND EVALUATION FOR SOCIAL DEVELOPMENT: A CASE FOR SOCIAL WORK IN SOUTH AFRICA - Noyoo, N (Social Work/Maatskaplike Werk, 2005)
It is now ten years since the transition from autocracy to democracy unfolded and seven years since the development welfare paradigm was formally adopted as South Africa's welfare policy. During this period momentous changes have transpired in the sector. Critical among these are the repealing of archaic racist and exclusive legislation or policies; shifting of programmatic foci to more inclusiveness and issue-based targets, e.g. poverty reduction; the transformation of the former Council of Social Work; refocusing of social work education and training to reflect the changed social order; and changing the financing regimes of the sector. Despite these positive endeavours, it is still difficult to ascertain systematically the efficacy of programmatic interventions, especially the way in which they have impacted positively upon the lives of vulnerable groups. The present discussion proposes that monitoring and evaluation (M&E) need further implementation and articulation in social development so as to address the aforementioned shortfall in this arena.